Identification of a novel NRF1::PDGFRA fusion in myeloid/lymphoid neoplasms with eosinophilia and tyrosine kinase gene fusions - Liu, Jialong; Feng, Yaqing; Zhang, Yanfang; Xiao, Yingnan; Liu, Xi; Xiao, Tingting; Zou, Junyan; Fan, Kai; Lu, Lisha; Yang, Xiaoxia; Gong, Jinying (Frontiers in Oncology, 2025)
A novel fusion gene NRF1::PDGFRA was identified in a patient with myeloid/lymphoid neoplasms with eosinophilia and tyrosine kinase gene fusions (MLN-TK), harboring the chromosome abnormality t(4;7)(q12;q32). This represents the first reported case of the NRF1::PDGFRA fusion gene, and the ninth PDGFRA-associated fusion gene identified in MLN-TK. The fusion event led to the constitutive activation of the PDGFRA kinase, resulting in uncontrolled eosinophil proliferation and potentially contributing to the occurrence of cerebral infarction. Our study indicates treatment with low-dose imatinib effectively alleviates the symptoms associated with NRF1::PDGFRA gene fusion.